Pastoral Counseling for Congregants Experiencing Work-place Discrimination Because of Christian Faith - Amos Hosea; Gernaida Krisna R. Pakpahan; Obaja Ari Budiman (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
This conceptual research article examines pastoral counseling for Christian congregants who experience discrimination because of their faith in workplace settings. The problem addressed is not only the organizational injustice of religious discrimination but also its psychological, relational, and spiritual consequences for believers who must negotiate professional responsibilities, Christian identity, and institutional vulnerability. The study aims to construct a pastoral-counseling framework that is theologically grounded, trauma-informed, ethically cautious, and practically useful for churches without claiming empirical findings from fieldwork. Using an integrative literature-review design, the article synthesizes scholarship on workplace religious discrimination, religious identity at work, perceived discrimination and mental health, religious coping, spiritual struggle, trauma-informed care, and pastoral theology. The synthesis identifies three major arguments: workplace faith discrimination should be interpreted as identity-related and spiritual injury rather than merely interpersonal discomfort; pastoral counseling must combine safe presence, lament, theological reframing, assessment of religious coping, and referral when needed; and churches should help congregants move from passive endurance toward prudent agency, documentation, accommodation-seeking, reconciliation where possible, and advocacy where necessary. The article concludes that pastoral counseling can become a constructive bridge between care and justice when it resists both victim-blaming and triumphalist persecution narratives.